(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In the article, the interaction of parts of speech in the field of word formation is manifested in different aspects. Each part of speech serves as the basis for the formation of words of certain lexicogrammatical categories. The interaction of parts of speech at the level of antonymic nests is a part of their life in the language, with which lexical-semantic, structural and formal-grammatical relationships are associated, characteristic of single-root words, as well as part-of-speech relationships are based on family ties of words, therefore they are especially close, close, significant, weighty. They have more organizing power than frequent-speech relations of different roots.